PRINCIPLES FOR IMPROVING THE METHODOLOGY FOR DEVELOPING THE PROFESSIONAL TRAINING OF FUTURE ENGINEERS USING DIGITAL TECHNOLOGIES (Educa Journal of Studies, 2026)
This article discusses the issues of developing the professional training of future engineers based on modern digital technologies. The possibilities of improving students' knowledge, skills and competencies through the effective use of digital tools in the educational process are analyzed. The main principles of improving the methodology of professional training are also developed.
Keywords: Digital technologies, engineering education, professional competence, innovative methods, interactive education.